Advances in group processes. Vol. 30 - Thye, Shane R.; Lawler, Edward J. (Advances in group processes., 2013)
This volume marks the 30th anniversary of the Advances in Group Processes Series. Publishing theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of "group processes." This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, exchange, justice, influence, decision-making, intergroup relations and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, philosophy, computer science, mathematics and organizational behaviour.